Protective effects of krill oil on ischemic reperfusion injury in experimental model of priapism - Kölükçü, Engin; Uluocak, Nihat; Unsal, Velid (Journal of Surgery and Medicine, 2019)
Aim: The aim of the study is to evaluate the effects of krill oil on priapism induced ischemia-reperfusion injury in priapism rat model. Methods: Total of 24 rats were randomly divided into three groups with eight rats in each group. Group 1 was determined as the control group. Experimental priapism model was constructed in rats in Groups 2 and 3 for 1 hour and then priapism was terminated for 30 minutes to evaluate ischemia-reperfusion injury. The rats in Groups 1 and 2 were given tap water and standard chow pellets. Group 3: The same feeding procedure was applied to the experimental animals but supplemented with krill oil for one month. At the end of the experiment penectomy were performed, and blood samples were withdrawn from inferior vena cava of the rats to determine the levels of protein carbonyl (PC), malondialdehyde (MDA), nitric oxide (NO), glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) in systemic circulation, and cavernosal tissues. Results: Biochemical examination of penile tissues showed that MDA and PC levels in Group 3 were significantly lower than group 2, while GSH-Px activities were significantly increased (P=0.001, P=0.005, P=0.003 respectively). Serum analysis results showed that MDA and NO levels in Group 3 were significantly lower than Group 2 and SOD activities significantly increased (P=0.011, P=0.001, P=0.009, respectively). Conclusion: In this study, protective effect of krill oil against priapism induced ischemia-reperfusion injury in cavernosal tissue was observed based on biochemical evidence.